The new frontiers of Article 102 TFEU: antitrust imperialism or judicious intervention?. (14th December 2017) - Bailey, David
Abstract: The purpose of this article is to examine whether and to what extent Article 102 of the Treaty on the Functioning of the European Union is being applied to more and more practices with less and less regard for the rules, procedures and remedies provided by other fields of law that also apply to those practices. It argues that the case-law and decisional practice under Article 102 reveals both signs of 'antitrust imperialism' and cases that, inevitably, turned on their particular facts and circumstances. It concludes by offering six propositions that appear to inform the application of Article 102 to conduct of dominant firms that is also subject to other legal rules.